2013
DOI: 10.5792/ksrr.2013.25.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Femoral Tunnel Length in Anterior Cruciate Ligament Reconstruction: CT Analysis of the Influence of Tunnel Orientation on the Length

Abstract: PurposeThe purpose of the study was to identify the femoral tunnel orientation that consistently results in a tunnel length of more than 35 mm in anterior cruciate ligament reconstruction.Materials and MethodsComputed tomography (CT) scans were obtained from 30 patients who did not have any pathology in the distal femur. Virtual tunnels were marked on 3D (3-dimensional) reconstructed CT images after determining the orientation defined by sagittal inclination and axial angle. The length of a femoral tunnel in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The lack of graft incorporation is a common cause of surgical failure [ 14 ]. Greis et al reported that the length of a tendon placed within a bone tunnel influences tendon pullout strength, and advocated maximizing the tendon length inside the bone tunnels [ 22 ]. Previous cadaveric and clinical studies reported that the mean femoral tunnel length drilled through AM portals ranges from 15.7 − 34.2 mm [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of graft incorporation is a common cause of surgical failure [ 14 ]. Greis et al reported that the length of a tendon placed within a bone tunnel influences tendon pullout strength, and advocated maximizing the tendon length inside the bone tunnels [ 22 ]. Previous cadaveric and clinical studies reported that the mean femoral tunnel length drilled through AM portals ranges from 15.7 − 34.2 mm [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thought it was necessary to investigate tunnel configurations made using curved guides with a three-dimensional approach because it allows a certain degree of control over intra-articular tunnel orientation. Few previous studies have investigated the ideal tunnel axis angle for longer tunnel lengths [ 22 , 28 ]. These studies were limited because they were experimental studies using a bone saw or cadaver, and the results are difficult to reproduce in a practical surgical situation.…”
Section: Discussionmentioning
confidence: 99%
“…The transportal guide wire was placed 30-45 in the sagittal plane and horizontal to the floor via the accessory anteromedial portal. 15 Then a 4.5 mm cannulated drill was used to drill a tunnel and the length was measured. Then the femoral tunnel was made larger as needed according to the width of the graft with flower head tipped drills.…”
Section: Operative Techniquementioning
confidence: 99%
“…The above concerns are magnified for anatomic ACL reconstructions, which utilize an anteromedial arthroscopic portal for femoral tunnel reaming and subsequently create shorter femoral tunnels, relative to the transtibial technique . Recent studies have demonstrated an ability to create femoral tunnels greater than 30 mm in length; however, Golish et al reported the median length to be 25 mm for anteromedial reamed tunnels which is consistent with the technique and experience of the senior surgeon. Therefore, the current study results are schematically represented in 25 mm femoral tunnels for ACL reconstruction (Fig.…”
Section: Discussionmentioning
confidence: 85%